Cancer-derived exosomes: mediators of immune crosstalk and emerging targets for immunotherapy - Mahamed, Ridwan; Monchusi, Bernice; Penny, Clement; Mirza, Sheefa (Frontiers in Immunology, 2025)
Exosomes, nanoscale extracellular vesicles secreted by various cell types, play pivotal roles in intercellular communication. In cancer, tumor-derived exosomes—referred to as cancer-derived exosomes (CDEs)—have emerged as critical regulators of immune evasion, tumor progression, and therapy resistance within the tumor microenvironment (TME). CDEs modulate immune cell function through the transfer of immunosuppressive proteins, cytokines, and non-coding RNAs, ultimately reprogramming immune surveillance mechanisms. This review provides an in-depth analysis of how CDEs influence major immune cell subsets—including T cells, B cells, NK cells, dendritic cells, macrophages, and myeloid-derived suppressor cells—thereby establishing an immunosuppressive TME. We also explore the potential of immune cell-derived exosomes (IDEs) as emerging immunotherapeutic tools capable of counteracting the suppressive effects of CDEs. Furthermore, we highlight exosome engineering strategies aimed at improving therapeutic cargo delivery, tumor targeting, and antitumor immune activation. Finally, we discuss how exosome profiling offers promise in liquid biopsy diagnostics and how integration with 3D tumor models and advanced bioengineering can accelerate the clinical translation of exosome-based cancer immunotherapies.